2019
DOI: 10.1016/j.isci.2019.08.055
|View full text |Cite
|
Sign up to set email alerts
|

N-Doped Mo2C Nanobelts/Graphene Nanosheets Bonded with Hydroxy Nanocellulose as Flexible and Editable Electrode for Hydrogen Evolution Reaction

Abstract: SummaryThe large-scale application of economically efficient electrocatalysts for hydrogen evolution reaction (HER) is limited in view of the high cost of polymer binders (Nafion) for immobilizing of powder catalysts. In this work, nitrogen-doped molybdenum carbide nanobelts (N-Mo2C NBs) with porous structure are synthesized through a direct pyrolysis process using the pre-prepared molybdenum oxide nanobelts (MoO3 NBs). Nanocellulose instead of Nafion-bonded N-Mo2C NBs (N-Mo2C@NCs) exhibits superior performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…The Tafel slope value of S-RuP@NPSC-900 (90.23 mV dec −1 ) was smaller than those of NPSC (364.36 mV dec −1 ), RuS 2 @NPSC-800 (352.67 mV dec −1 ), and S-RuP@NPSC-1000 (106.19 mV dec −1 ), and was larger than that of 20 wt% Pt/C (60.30 mV dec −1 ), confirming the desorption of H* (either the ion and atom reaction) was the ratedetermining step in HER reaction process (Heyrovsky-Volmer reaction). [9,32,45,46] It was worth emphasizing that RuS 2 @NPSC-800, S-RuP@NPSC-900, and S-RuP@NPSC-1000 possessed the ultralow loading amounts of Ru measured by ICP, which were 0.73, 0.8, and 0.85 wt%, respectively. Area and mass specific activity of RuS 2 @NPSC-800, S-RuP@NPSC-900, S-RuP@NPSC-1000, and 20 wt% Pt/C with the overpotential of 250 mV were calculated by the content of precious metals of Ru and Pt.…”
Section: Resultsmentioning
confidence: 99%
“…The Tafel slope value of S-RuP@NPSC-900 (90.23 mV dec −1 ) was smaller than those of NPSC (364.36 mV dec −1 ), RuS 2 @NPSC-800 (352.67 mV dec −1 ), and S-RuP@NPSC-1000 (106.19 mV dec −1 ), and was larger than that of 20 wt% Pt/C (60.30 mV dec −1 ), confirming the desorption of H* (either the ion and atom reaction) was the ratedetermining step in HER reaction process (Heyrovsky-Volmer reaction). [9,32,45,46] It was worth emphasizing that RuS 2 @NPSC-800, S-RuP@NPSC-900, and S-RuP@NPSC-1000 possessed the ultralow loading amounts of Ru measured by ICP, which were 0.73, 0.8, and 0.85 wt%, respectively. Area and mass specific activity of RuS 2 @NPSC-800, S-RuP@NPSC-900, S-RuP@NPSC-1000, and 20 wt% Pt/C with the overpotential of 250 mV were calculated by the content of precious metals of Ru and Pt.…”
Section: Resultsmentioning
confidence: 99%
“…Another important industrial application of nanocellulose/graphene composites is in energy storage, generation and conversion. Devices for these purposes include supercapacitors [64,80,130], hydrogen storage devices [131], electrodes for hydrogen evolution reaction [132], lithium ion batteries [133], actuators [81], solar steam generators [82] and electric heating membranes [83]. These devices can be based on pure nanocellulose/nanocarbon composites without additives [80][81][82][83].…”
Section: Preparation and Industrial Application Of Nanocellulose/grapmentioning
confidence: 99%
“…However, they often contain additives such as manganese oxide (MnO), which contributes to faradaic pseudocapacitance in supercapacitors [130] or polypyrrole, which acts as an insulator, but its oxidized derivatives are good electrical conductors [134]. Other additives are palladium or platinum nanoparticles for enhanced hydrogen storage [131], nitrogen-doped molybdenum carbide nanobelts in electrocatalysts for hydrogen evolution reaction [132], and silicon oxide nanoparticles in lithium ion batteries [133].…”
Section: Preparation and Industrial Application Of Nanocellulose/grapmentioning
confidence: 99%
“…[3][4][5] Experimental findings revealed that the kinetics (expressed in exchange current density, j o ) of the HER in alkaline media is lower than that in acidic ones by 2 to 3 orders of magnitude. [6][7][8][9] Even on Pt, the most promising and highly efficient electrocatalyst for the HER, owing to its high reactivity for the adsorption and recombination of reactive H ads , 10 the HER exhibited slower kinetics in alkaline solutions, as compared to acidic ones. 11 The reduced efficacy of the water dissociation step on the Pt surface, Equation 6which constitutes an additional energy barrier to the kinetics of the overall reaction rate, is the main reason behind the sluggish kinetics of the alkaline HER on Pt surface.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous publications reported that the HER on a wide range of electrocatalysts is pH‐dependent, generally decreases with increasing pH 3‐5 . Experimental findings revealed that the kinetics (expressed in exchange current density, j o ) of the HER in alkaline media is lower than that in acidic ones by 2 to 3 orders of magnitude 6‐9 . Even on Pt, the most promising and highly efficient electrocatalyst for the HER, owing to its high reactivity for the adsorption and recombination of reactive H ads , 10 the HER exhibited slower kinetics in alkaline solutions, as compared to acidic ones 11 .…”
Section: Introductionmentioning
confidence: 99%